Fern inventorization in Laiwangi-Wanggameti National Park, East Sumba, Waingapu, NTT - I DEWA PUTU DARMA; I NYOMAN PENENG (Society for Indonesian Biodiversity, 2007)
The inventory and the collection of the ferns in Laiwangi Wanggameti National Park will be plamted as collection plants in Bali Botanical Garden. In this research used the explorative method. The result of the research has collected 70 numbers of the ferns and 229 speciment. They consist of 21 family, 30 genus.and 70 species. From 70 species. There are 3 species such as Licopodium sernuum, Lygodium javanicum (Tumb.) Sw. and Ophioglossum pendulum L. are predicted as new collection for the Bali Botanic Garden. The dominant genus in Laiwangi- Wanggameti National Park was Cyclosorus, Asplenium, Athyrium, and Pteris. Which are growing to coverthe basic of the forest in damp places at the river bank.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: inventory, collections, ferns, Laiwangi-Wanggameti National Park.